2012
DOI: 10.1371/journal.pcbi.1002635
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Gap Gene Expression in Drosophila Kruppel Mutants

Abstract: The segmentation gene network in Drosophila embryo solves the fundamental problem of embryonic patterning: how to establish a periodic pattern of gene expression, which determines both the positions and the identities of body segments. The gap gene network constitutes the first zygotic regulatory tier in this process. Here we have applied the systems-level approach to investigate the regulatory effect of gap gene Kruppel (Kr) on segmentation gene expression. We acquired a large dataset on the expression of gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 83 publications
1
60
0
Order By: Relevance
“…and relative strengths of e®ects on hb transcription that best¯t the experimental pattern. We focus on expression of the PS4 stripe: computations are run on the interval 18-65%EL, which does not include the posterior stripe (and which is likely under di®erent TF controls 12,27,36 ). For this, we use the approximation that P1 control is through the stripe element only, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and relative strengths of e®ects on hb transcription that best¯t the experimental pattern. We focus on expression of the PS4 stripe: computations are run on the interval 18-65%EL, which does not include the posterior stripe (and which is likely under di®erent TF controls 12,27,36 ). For this, we use the approximation that P1 control is through the stripe element only, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Gt and Kni shift in Kr À mutants; for modeling these cases, we used input data from Ref. 36. Initial values of hb P1 and P2 mRNA were set to zero.…”
Section: Input Data and Data To¯tmentioning
confidence: 99%
“…For example, parameter searches with the gene interaction matrix approach of Mjolsness et al and Reinitz and Sharp [8,9] found classes of networks for wild-type [10] and mutant [11][12][13] gap-gene patterns. Such potential mechanisms can be further screened for robustness to extrinsic variability, such as to Bcd gradient variability [11,12].…”
Section: Regulatory Mechanisms For Robust Gene Expressionmentioning
confidence: 99%
“…The equation (1) is widely applied for description of diffusive transport, e.g., of protein transfer, that are synthesized by gap genes (the gene expression process) in D.melanogaster embryo at the early stages of development [10,13]. However, it is well known, that the model (1) has a remarkable disadvantage [1]: the propagation velocity of perturbations is infinite.…”
Section: Introductionmentioning
confidence: 99%